Consumer preferences and brand equity measurement of Spanish national daily newspapers: A conjoint analysis approach. - Rial Bobueta, Antonio; Varela Mallou, Jesús; Braña Tobío, Teresa (The Spanish Journal of Psychology, 2001)
Sin resumen